2006
DOI: 10.1111/j.1461-0248.2006.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites for ecologists: a practical guide to using and evaluating microsatellite markers

Abstract: Recent improvements in genetic analysis and genotyping methods have resulted in a rapid expansion of the power of molecular markers to address ecological questions. Microsatellites have emerged as the most popular and versatile marker type for ecological applications. The rise of commercial services that can isolate microsatellites for new study species and genotype samples at reasonable prices presents ecologists with the unprecedented ability to employ genetic approaches without heavy investment in specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
1,106
6
33

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,343 publications
(1,165 citation statements)
references
References 126 publications
(224 reference statements)
20
1,106
6
33
Order By: Relevance
“…Non‐hierarchical analyses of molecular variance were performed with arlequin using the microsatellite‐specific R ‐statistics (Slatkin 1995; Selkoe and Toonen 2006). Furthermore, we calculated pairwise D est values (Jost 2008) across all populations (excluding Eburu Forest, due to very small sampling size) with the program smogd v.1.2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Non‐hierarchical analyses of molecular variance were performed with arlequin using the microsatellite‐specific R ‐statistics (Slatkin 1995; Selkoe and Toonen 2006). Furthermore, we calculated pairwise D est values (Jost 2008) across all populations (excluding Eburu Forest, due to very small sampling size) with the program smogd v.1.2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Of the various types of molecular markers used today, microsatellites have many positive attributes, including hypervariability, co-dominance, abundance and tolerance to variation in DNA quality and quantity (Selkoe and Toonen, 2006). Additionally, due to our reasonably good understanding of molecular evolution and the development of robust computational methods, microsatellites are wellsuited to answer questions related to effective population size, population structure, migration and colonization rates, and reproductive system, thus providing essential data for conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Although mutations in the flanking regions of microsatellite loci may prevent amplification, many studies have shown that microsatellites isolated from one species can amplify homologous products in related species (e.g. Martínez-Cruz et al, 2002;Busch et al, 2005), a characteristic known as transferability or cross-species amplification (Selkoe and Toonen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian inheritance, combined with high levels of polymorphism, makes microsatellite loci ideal for these purposes and for analyses of small and isolated populations, like blue-footed boobies (Hedrick 1999;Selkoe and Toonen 2006). In this manuscript, we describe the isolation and characterization of 11 microsatellite loci, which we tested using 31 S. nebouxii.…”
mentioning
confidence: 99%